2011
DOI: 10.1371/journal.pone.0026543
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sympathetic Nervous System Genes in Lamprey Suggests Their Recruitment for Specification of a New Vertebrate Feature

Abstract: The sea lamprey is a basal, jawless vertebrate that possesses many neural crest derivatives, but lacks jaws and sympathetic ganglia. This raises the possibility that the factors involved in sympathetic neuron differentiation were either a gnathostome innovation or already present in lamprey, but serving different purposes. To distinguish between these possibilities, we isolated lamprey homologues of transcription factors associated with peripheral ganglion formation and examined their deployment in lamprey emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…A recent study in lamprey (37) showed a contribution of the trunk crest but not of the vagal crest to the ENS. Since agnathans are suggested to have no sympathetic neural crest derivative (38), the absence of vagal contribution to the ENS fits with our data that the formerly called "vagal" crest of gnathostomes is for the most part cervical and sympathetic; but it also entails the surprising notion that the vagus nerve itself does not carry Schwann cell precursors-like enteroblasts to the gut of lampreys, when trunk nerves do.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study in lamprey (37) showed a contribution of the trunk crest but not of the vagal crest to the ENS. Since agnathans are suggested to have no sympathetic neural crest derivative (38), the absence of vagal contribution to the ENS fits with our data that the formerly called "vagal" crest of gnathostomes is for the most part cervical and sympathetic; but it also entails the surprising notion that the vagus nerve itself does not carry Schwann cell precursors-like enteroblasts to the gut of lampreys, when trunk nerves do.…”
Section: Discussionsupporting
confidence: 84%
“…In ascidians, Phox2 expression is limited at larval stages to neurons in the region proposed to be homologous with the vertebrate brainstem, and in the sessile adult is present in neurons associated with the branchial arches (Dufour, Chettouh, Deyts, De Rosa, Goridis, Joly and Brunet, 2006). In lampreys, Phox2 expression is limited to the brainstem, and although its expression in motor neurons has not yet been demonstrated directly, it likely overlaps with motor neurons associated with cranial nerves III–X (Häming, et al, 2011) (lampreys have neither a hypoglossal nerve (they are jawless and tongue-less) nor an accessory nerve (associated with muscles of anterior appendages, absent in lamprey) (Fritzsch and Northcutt, 1993a). …”
Section: Evolution Of Phox2-dependent Brainstem Motor Neuronsmentioning
confidence: 99%
“…It has not yet been demonstrated whether Phox2 gene(s) are expressed in lamprey extraocular muscle motor neurons [(Häming, Simoes-Costa, Uy, Valencia, Sauka-Spengler and Bronner-Fraser, 2011) III, IV, VI] and if those motor neurons are dependent on Phox2 expression, as they are on Phox2a in mice (Pattyn, Morin, Cremer, Goridis and Brunet, 1997). It would also be interesting to determine whether hagfish (another cyclostome that separated from a common ancestor with the lampreys about 350 million years ago, (Simakov, Kawashima, Marlétaz, Jenkins, Koyanagi, Mitros, Hisata, Bredeson, Shoguchi and Gyoja, 2015)), which lack extraocular muscles and their innervating cranial nerves (III, IV and VI), exhibit any transient expression of Phox2 in the developing midbrain/hindbrain region where the III and IV nuclei normally develop.…”
Section: Evolution Of Phox2-dependent Brainstem Motor Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lampreys are basal vertebrates that lack several neural crest derivatives, including a neural crest-derived jaw and sympathetic ganglia (Nicol 1952;Häming et al 2011). Nevertheless they possess a SoxE expressing population of migrating neural crest cells (McCauley and Bronner-Fraser 2006) that contribute to branchial arch cartilage, as well as the formation of pigment cells, cranial, and dorsal root ganglia.…”
Section: Evolutionary Conservation Of the Neural Crest Grnmentioning
confidence: 99%